Developing podcast for listening material for grade 10 - Anggriani, Titania; Elfiza, Rona; Candra, Muhammad (Juliet, 2024)
This study aimed to developedpodcast for listening material for grade 10. The subject of this research was the tenth grade, which consisted of 22 students. The location of this research was in the MAN Tanjungpinang. The type of this research was development research with ADDIE model. The researcher focused on developing podcast for listening matrial that was suitable for students’ daily activity and their environment. There were five stages namely analysis, design, development, implementation and evaluation. The data obtained from students’ need questionnaires, expert validation questionnaire, and small group try out questionnaire. The results showed that the podcast validation results for students' listening material for class X were valid and did not need revisions. Podcasts were directly implemented to students. Based on the results of student implementation of the practicality test sheet, it was found that podcasts for listening material for grade 10 were very appropriate and practical.